Biodegradable cationic poly(carbonates): Effect of varying side chain hydrophobicity on key aspects of gene transfection. (May 2017) - Ong, Zhan Yuin; Yang, Chuan; Cheng, Wei; Voo, Zhi Xiang; Chin, Willy; Hedrick, James L.; Yang, Yi Yan
Graphical abstract: Abstract: The degree of hydrophobicity in cationic polymers plays an important but often underappreciated role in the safety and efficacy of gene delivery processes. In order to further elucidate structure-activity relationships of biodegradable cationic poly(carbonate) gene carriers, we synthesized a series of narrowly dispersed homo-polymers via metal-free organocatalytic living ring-opening polymerization (ROP) of cyclic carbonate monomers bearing either alkyl (propyl, hexyl or nonyl) or 4-methyl benzyl halide side chains. The polymers were then quaternized using bis-tertiary amines to install both quaternary ammoniums and tertiary amines for DNA binding and endosomal escape, respectively. Among the polymers with similar molecular lengths and charge densities, it was found that an increase in side chain alkyl spacer length from 3 to 6 carbons significantly enhanced cellular uptake and luciferase gene expression in HepG2 and HeLa cell lines without causing overt hemolysis and cytotoxicity. A further increase of side chain alkyl length to 9 carbons, however, led to a drastic decline in gene expression due to increased cellular toxicity, which was correlated with an increased disruption and lysis of red blood cell membranes. Interestingly, the incorporation of an aromatic 4-methyl benzyl spacer increased DNA binding strength, reduced particle sizes of resultant DNA complexes, and enhanced cellular uptake, leading to improved luciferase gene expression, albeit with higher levels of hemolysis and cytotoxicity. Taken together, the findings of this study demonstrate that a delicate balance between cationic charge density and hydrophobicity could be achieved by utilizing a hexyl spacer in the side chains of cationic poly(carbonates), hence providing insights on the future development of non-viral cationic polymeric gene delivery systems. Statement of Significance: Owing to their ease of synthesis and well-controlled polymerization, biodegradable cationic poly(carbonates) have emerged as a highly promising class of biomaterials for gene delivery. The hydrophobicity of side chains in cationic polymers plays an important but often underappreciated role in influencing key aspects of gene transfection. In our efforts to improve gene transfection and understand structure-activity relationships, we synthesized a series of cationic polymers bearing a common poly(carbonate) backbone, and with side chains containing various hydrophobic spacers (propyl, hexyl, 4-methyl benzyl or nonyl) before the cationic moiety. A moderate degree of hydrophobicity was optimal as the cationic poly(carbonate) with hexyl side chains mediated high gene transfection efficiencies while causing low cytotoxicities.